2014
DOI: 10.1093/hmg/ddu190
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of senataxin alters disease-specific transcriptional networks in patients with ataxia with oculomotor apraxia type 2

Abstract: Senataxin, encoded by the SETX gene, contributes to multiple aspects of gene expression, including transcription and RNA processing. Mutations in SETX cause the recessive disorder ataxia with oculomotor apraxia type 2 (AOA2) and a dominant juvenile form of amyotrophic lateral sclerosis (ALS4). To assess the functional role of senataxin in disease, we examined differential gene expression in AOA2 patient fibroblasts, identifying a core set of genes showing altered expression by microarray and RNA-sequencing. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Of the several WGCNA studies reported utilizing expression data from patients with neurodegenerative disease, two of note in relation to our work are a WGCNA using data from brain and peripheral tissues of patients with ataxia with oculomotor apraxia type 2 (AOA2) and an analysis of brain expression data, including data from the cerebellum, from patients with C9orf72 associated and sporadic amyotrophic lateral sclerosis (ALS) (Fogel et al, 2014; Prudencio et al, 2015). AOA2 is due to recessive mutations in the Senataxin ( SETX ) gene while ALS4 is a juvenile form of ALS caused by dominant SETX mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Of the several WGCNA studies reported utilizing expression data from patients with neurodegenerative disease, two of note in relation to our work are a WGCNA using data from brain and peripheral tissues of patients with ataxia with oculomotor apraxia type 2 (AOA2) and an analysis of brain expression data, including data from the cerebellum, from patients with C9orf72 associated and sporadic amyotrophic lateral sclerosis (ALS) (Fogel et al, 2014; Prudencio et al, 2015). AOA2 is due to recessive mutations in the Senataxin ( SETX ) gene while ALS4 is a juvenile form of ALS caused by dominant SETX mutations.…”
Section: Discussionmentioning
confidence: 99%
“…An important future goal will be to identify the molecular defects that are associated with clinically relevant mutations in senataxin. Analysis of transcription in cells carrying AOA2- or ALS4-causing mutations revealed disease-specific effects on the expression of numerous genes (170). Providing molecular insight into some AOA2 mutations is the recent finding that a SUMOylation-mediated interaction between the N-terminal region of senataxin and the exosome protein Rrp45 is disrupted by AOA2-causing mutations in senataxin (171).…”
Section: Connections To Cell Physiology: Yeast and Humansmentioning
confidence: 99%
“…ZGRF1 also belongs to the family of UPF1-like RNA helicases that are involved in aspects of DNA replication and repair, transcription regulation, RNA metabolism, genome integrity or topoisomerase activities. Mutations in genes belonging to this family have been implicated in neurological conditions like distal spinal muscular atrophy (IGHMBP2; Grohmann et al, 2001), spinocerebellar ataxia and amyotrophic lateral sclerosis (SETX; Fogel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%